Cystic fibrosis identified by neonatal screening: incidence, genotype, and early natural history. Issue 4 (April 1993) - Green, M R; Weaver, L T; Heeley, A F; Nicholson, K; Kuzemko, J A; Barton, D E; McMahon, R; Payne, S J; Austin, S; Yates, J R
Abstract : The incidence of cystic fibrosis over the last 10 years in East Anglia (a region of the United Kingdom with a population of 2.1 million) has halved. This has happened during the establishment of a neonatal screening programme, which has enabled early diagnosis, genetic counselling, and lately the option of prenatal diagnosis in subsequent pregnancies. One hundred and seven children were born with cystic fibrosis between 1981 and 1990, eight of whom were siblings. The Guthrie blood spots of 82 infants detected by neonatal immunoreactive trypsin screening between 1981 and 1990 were examined for the presence of the most common cystic fibrosis gene mutation (delta F508). It was present in 135 (82%) of the 164 cystic fibrosis genes analysed with 54 (66%) cases being homozygous and 27 (33%) heterozygous. Sixty nine per cent of infants were symptomatic at the time of diagnosis regardless of genotype. No association was found between the early clinical or biochemical features of the disease and homozygosity or heterozygosity for this mutation. Screening for cystic fibrosis using the blood immunoreactive trypsin assay alone remains an effective method of identifying infants with the disease soon after birth, thereby allowing early therapeutic intervention. Genetic counselling and prenatal diagnosis have contributed to a reduction in the number of children born with cystic fibrosis, but may not entirely explain the decreasing incidence of the disease.